Effects of Electrodeposition Mode and Deposition Cycle on the Electrochemical Performance of MnO(2)-NiO Composite Electrodes for High-Energy-Density Supercapacitors - Rusi (PLoS One, 2016)
Nanostructured network-like MnO(2)-NiO composite electrodes were electrodeposited onto stainless steel substrates via different electrodeposition modes, such as chronopotentiometry, chronoamperometry, and cyclic voltammetry, and then subjected to heat treatment at 300°C for metal oxide conversion. X-ray diffraction, field emission scanning electron microscopy, and transmission electron microscopy were used to study the crystalline natures and morphologies of the deposited films. The electrochemical properties were investigated using cyclic voltammetry and charge/discharge tests. The results revealed that the electrochemical performance of the as-obtained composite electrodes depended on the electrodeposition mode. The electrochemical properties of MnO(2)-NiO composite electrodes prepared using cyclic voltammetry exhibited the highest capacitance values and were most influenced by the deposition cycle number. The optimum specific capacitance was 3509 Fg(−1) with energy and power densities of 1322 Wh kg(−1) and 110.5 kW kg(−1), respectively, at a current density of 20 Ag(−1) in a mixed KOH/K(3)Fe(CN)(6) electrolyte.